Sistema de avaliação da educação do estado do Rio de Janeiro - SAERJ: fundamentos e aplicações - Jurgensen, Karina Yara [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Taking into account the external evaluations, currently, have got a strong expression on the national scene through the implementation and systematization of national assessment system, known as the Sistema Nacional de Avaliação de Educação Básica (SAEB) elaborated with the objective of improving the quality of education in public schools and consequently encouraging the Brazilian states to create their own evaluation systems. This work aims to analyze the external evaluation of the state of Rio de Janeiro known as SAERJ (Sistema de Avaliação da Educação do Estado do Rio de Janeiro). From this research, it is intended to characterize how is organized this evaluation system, what their guidelines and understandings of assessment, their origin and characteristics, how it is organized and applied to identify the foundations that support this assessment system. Initially it was necessary to use a qualitative research approach to characterize the evaluation system studied. For the developing of the research, the methodology used will be bibliographic and documentary character, in which will be detailed information and data on these assessments with other authors and legislation dealing with the same theme. Therefore, we intend through the results, carry out further on data about the system under study and evaluation of the fundamentals proposed in the state of Rio de Janeiro and Espirito Santo

Considerando que as avaliações externas atualmente tem ganhado forte expressão no cenário nacional por meio da implantação e sistematização do sistema de avaliação nacional, conhecido como Sistema Nacional de Avaliação de Educação Básica (SAEB) elaborado sob a justificativa de melhorar a qualidade de ensino nas escolas públicas e, consequentemente, incentivando os estados brasileiros a criação de seus próprios sistemas de avaliação; este trabalho tem como objetivo conhecer e entender o Sistema de Avaliação da Educação do Estado do Rio de Janeiro - SAERJ. A partir dessa pesquisa, se pretende caracterizar como se organiza este sistema de avaliação, quais suas orientações sobre avaliação, sua origem e características, como é organizado e aplicado. Inicialmente se faz necessário recorrer a uma pesquisa de abordagem qualitativa para caracterizar o sistema de avaliação estudado e a metodologia utilizada será de caráter bibliográfico e documental, nos quais serão aprofundados as informações e os dados acerca dessas avaliações junto à literatura especializada e a legislação que tratam do mesmo tema. Portanto, almeja-se através dos resultados obtidos, realizar um aprofundamento sobre dados acerca do sistema estudado e dos fundamentos da avaliação proposta no estado do Rio de Janeiro
Keywords: Sistema Nacional de Avaliação de Educação Básica (Brasil); Avaliação educacional; Educação e Estado; Escolas públicas; Rio de Janeiro (Estado)